IMPLEMENTATION OF THE USE OF NATURAL ILLUSTRATIONAL IMAGE MEDIA FOR CHILDREN'S LEARNING CONCENTRATION - Masdar, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to increase learning concentration through the implementation of the use of naturalist illustration media. In order to obtain data from research results, research was carried out with a qualitative approach and a type of case study. Data collection technique with the technique of snowball sampling. The data sources used are primary and secondary. The subjects of this study were teaching staff and class VI students at MI Tarbiyah Islamiyah Paiton Probolinggo, which consisted of 33 students. Data collection techniques used participant observation, in-depth interviews, and documentation. Meanwhile, data analysis techniques used the Miles Huberman model, which included data reduction, data display, and conclusion. This study's results indicate that using naturalist illustration media for children's learning concentration at MI Tarbiyah Islamiyah Sidodadi Paiton, including planning, implementation, and evaluation, has been carried out well. The results of learning that is done can increase the level of concentration of children. The learning objectives will be achieved when the child can increase his concentration. The achievement of these goals will produce good graduates, thereby increasing the quality of schools. Teachers have also been active in teaching and guiding children to be active in learning in class. The form of evaluation is in the form of daily tests, homework, and end-of-semester exams. The questions given are memorization, counting pictures, reading, question and answer, etc.